Emergency medicine management training for scouts of Kwarda DIY: Improving disaster response capacity - Ghozali, Muhammad Thesa; Widada, Hari; Anggraini, Laelia Dwi; Styawan, Anita Agustina; Septiyanna, Rosemaladewi; Nisa, Lia Fakila; Faatin, Salsa (Universitas Muhammadiyah Magelang, 2025)
Indonesia’s high disaster vulnerability necessitates highly competent emergency medical response volunteers. This training program aimed to enhance the emergency medicine management skills of Disaster Response Scouts in the Yogyakarta Special Region (DIY). Thirty participants from five sub-districts (Gunungkidul, Sleman, Kulonprogo, Bantul, and Yogyakarta City) attended the training held May 19, 2024, at the DIY Regional Scout Hall. The training integrated mini-lectures, small group discussions, and hands-on practice for a holistic approach to theory and practical skills. Pre-test and post-tests, along with simulation observations, evaluated the training's effectiveness. Results showed a significant increase in average scores from 50.83 (pre-test) to 86.25 (post-test, p < 0.0001, Wilcoxon Test), with 66.7% of participants achieving “very good” status post-training (compared to 13.3% pre-training). This training enhanced not only participant knowledge and skills but also fostered collaboration among DIY Regional Scouts, health institutions, and academia.